105k views
2 votes
A(n) = A(n-1) + 5.1; A(1) = 9.6

User Mikl
by
5.4k points

1 Answer

4 votes

Answer:

A(n) = 5.1×n + 4.5

Explanation:

A(n) = A(n-1) + 5.1

A(1) = 9.6

A(n) - A(n-1) = 5.1 ,where n ≥ 1

This means that (A(n)) is an arithmetic sequence where :

The common difference r = 5.1

and

The first term A(1) = 9.6

Therefore

A(n) = A(1) + (n - 1)×r

= 9.6 + (n - 1)×5.1

= 9.6 + 5.1×n - 5.1

= 5.1×n + (9.6 - 5.1)

= 5.1×n + 4.5

User Levan
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.